Gallbladder hemorrhage during orally administered edoxaban therapy: a case report - Hideya Itagaki (Journal of Medical Case Reports, 2019)
Abstract Background Edoxaban is an orally administered anticoagulant treatment that is used in patients with cerebral infarction, venous thrombosis, or other conditions, with a reported incidence of gastrointestinal hemorrhage at approximately 1%. We encountered the rare case of a patient who developed a gallbladder hemorrhage after the administration of edoxaban. Case presentation An 86-year-old Japanese woman visited our gastrointestinal department due to the chief complaint of melena lasting for a week. Her medical history included hypertension and embolic cerebral infarction, and she was taking orally administered carvedilol (5 mg/day) and edoxaban (30 mg/day). Her palpebral conjunctiva was pale during a physical examination, indicating the possibility of anemia. Her blood test results confirmed severe anemia with red blood cells at 1.7 × 106/μL and hemoglobin at 4.7 g/dL. An upper gastrointestinal endoscopy revealed bile and fresh blood on the duodenal bulb and in more distal regions; hemobilia was suspected. A computed tomography scan on the ninth hospitalization day confirmed the hemobilia with a gallbladder fundus high-density signal. She was discharged on the 30th day of hospitalization with only fluid therapy and no progression of anemia. Moreover, she underwent a laparoscopic cholecystectomy 1 month after discharge, but the pathologist did not identify false aneurysms or neoplastic lesions. She has not been shown to develop anemia for 5 months after surgery. Conclusions Our case suggests that gallbladder hemorrhage needs to be considered a possible complication for patients on direct oral anticoagulants.